DETERMINATION OF THRESHOLD CURRENT DENSITIES FOR DIFFERENT REACTION OF FISHES USING A PANTOSTST - BISWAS, K P (Fishery Technology, 2025)
The threshold current densities required for first reaction, galvanotaxis and galvanonarcosis of fish depended upon species, length of the body. conductivity of water, nature of current and frequency of impulses. The threshold values and their ratios decreased with increase in length of fish. With rise in conductivity of water in . the ratio of 1:4:13, these values increased in the ratio 1 : 2 :-5; -Impulse D. C was superior to continuous D. C and the threshold values of current densities for different reactions of fish decreased with rise in impulse frequency reaching minimum at an impulse frequency of 48/sec. Among Safmo irideus, ldus melanotus and Cyprinus carpio, the first one was affected earlier and required minimum current densities to exhibit the reactions, while the last one showed similar reactions only at higher current densities.